Inactivity in Hungary - the persistent effect of the pension system - Zsombor Cseres-Gergely (Hungarian Academy of Sciences, Institute of Economics, 2007)
This paper looks at one of the major contributor to low overall employment rate in Hungary, the very low activity of the elderly. Although there are scattered pieces of evidence about the social security system in general having substantial influence on incentives and activity, the actual mechanisms are not well documented. Examining the incentive structure of the Hungarian old-age and disability pension system reveals that it provides very little to no incentive for extending active working life. Retirement through either of these pensions was and in 2006 still is an accessible exit route from the labour market that provides a minimal but secure income flow. For those reaching the minimum legal retirement age, retirement is so attractive compared to staying in the labour market that most of the working individuals retire. I use a simple model to estimate the incentives affecting the decision to retire before the legal age. Results from binary decision models estimated on household panel data support the hypothesis that incentives provided jointly by the labour market and the pension system make retirement very attractive, especially for those with bad labour market prospects. Accepting that this system was necessary to "mop up" excess labour supply in certain segments of the labour market (such as that of the extremely low-skilled individuals), it is not clear from a purely efficiency point of view why such a system is still in operation in 2006. (Remark: the government is planning to reform the system during 2007)
Keywords: J22; J26; J14; C34; 330; Time Allocation and Labor Supply; Retirement; Retirement Policies; Economics of the Elderly; Economics of the Handicapped; Truncated and Censored Models; Altersvorsorge; Altersgrenze; Erwerbstätigkeit; Arbeitsangebot; Ungarn